The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1093/jrr/rrad095
|View full text |Cite
|
Sign up to set email alerts
|

Anti-radiation effect of MRN-100: a hydro-ferrate fluid, in vivo

Mamdooh Ghoneum,
Nariman K Badr El-Din,
Mai Alaa El-Dein

Abstract: Ionizing radiation (IR) severely harms many organs, especially the hematopoietic tissue, mandating the development of protective nutraceuticals. MRN-100, a hydro-ferrate fluid, has been shown to protect γ-radiated fish against hematopoietic tissue damage and lethality. The current study aimed to examine MRN-100’s protective effect against irradiated mice and explore the mechanisms underlying its effect. Mice received a single acute, sub-lethal, 5 Gy, whole body dose of X-ray IR. MRN-100 treatment was administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…SrFeO 3−δ -based materials are the most widely studied for cathodes in iron-based systems. Other researchers have shown that the structure of SrFeO 3−δ varies significantly with the temperature and oxygen partial pressure [24][25][26][27][28][29][30][31][32][33][34][35][36]. Jiang et al introduced high-valence Nb into Fe and found that the modification of Nb enhanced the stability of the crystal and effectively avoided the phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…SrFeO 3−δ -based materials are the most widely studied for cathodes in iron-based systems. Other researchers have shown that the structure of SrFeO 3−δ varies significantly with the temperature and oxygen partial pressure [24][25][26][27][28][29][30][31][32][33][34][35][36]. Jiang et al introduced high-valence Nb into Fe and found that the modification of Nb enhanced the stability of the crystal and effectively avoided the phase transition.…”
Section: Introductionmentioning
confidence: 99%